Presenting complex, balanced scorecard model and two-level data envelopment analysis for calculating the performance of social institutions - Mehrdad Navabakhsh; Nasser Shahsavari Pour (Computational Algorithms and Numerical Dimensions)
Until the 1980s, the system for assessing the performance of organizations with specific structures has been based on economic and financial indexes. The previous methods that were frequently used for performance assessment were mainly focused on the economic-financial aspects of the organization. However, at present, due to vast human needs, sensitive cognitive, fundamental parameters in social organizations that are based on realities, are very effective, and meet scientific criteria have come into vogue. These parameters rely on experience, observation, experiment, hypothesis, and theory. Balanced Scorecard (BSC) seeks to make a balance between financial and economic objectives as outcomes of past performance (past-oriented indexes) and three indexes of customer processes, learning and growth, and development of human and social forces (future-oriented).Data Envelopment Analysis (DEA) is a non-parametric method for measuring the outputs or efficiency of homogeneous units with different inputs and outputs. However, in cases where there are numerous inputs and outputs with some similarities, their efficiency can be measured by two-level DEA, i.e., classifying them and using common weights.In primitive social institutions, the inputs of social systems are mainly limited and clear. However, in modern, complex, standardized systems, the input is both expanded and diversified. Therefore, in this paper, we have tried to use BSC as an instrument for designing performance assessment indexes and two-level DEA as an instrument for measurement.